Abuse in assisted reproductive technology: A systematic qualitative review and typology. (July 2019) - Hodson, Nathan; Bewley, Susan
Abstract: Objectives: Abuse of vulnerable patients exists in many healthcare settings and has been recognised as an inherent risk in assisted reproductive technology (ART). Systematic reviews have been used to develop typologies of abuse and ethical issues in other settings including obstetrics. The aim was to determine the full spectrum of abuse that patients can experience when using assisted reproductive technology. Study Design: A systematic qualitative review. MEDLINE, CINAHL, and PsycINFO were searched for combinations of terms related to abuse and terms relating to ART. The last search was performed on February 12 th 2018. Selection criteria were that the authors reported evidence of abuse. There were no exclusions by date, language or methodology. Papers lacking analysis of abuses in ART were excluded. For data collection and analysis, themes identified in the academic literature were coded using thematic qualitative analysis by two independent researchers. Themes were developed discursively. Results: There were 381 publications of which 44 full text articles were screened. The 34 included papers detailed abuses from 4 decades and 5 continents. There were no quantitative papers measuring prevalence. The resulting coding framework was presented as a typology of abuse in assisted reproductive technology with three first order themes: exploitation of class-based vulnerabilities, excessive intervention, and failures of aftercare. Conclusions: A wide range of categories of abuse was found despite the paucity of formal literature. A concerted public health approach to infertility is required, combined with an emphasis on trying conservative approaches first. More primary research is required on prevalence of abuse, and values and preferences, particularly in "egg sharing" and post-mortem reproduction.